WHEN CLASS DEFINES ART AND MARRIAGE APPROVAL: A MARXIST ANALYSIS OF THE GREATEST SHOWMAN - Saputro, Galih Yoga; Setianingsih, Fauziah; Azizah, Kuni Maskurotal (Fakultas Ilmu Budaya Universitas Jenderal Soedirman, 2018)
This research is descriptive qualitative research with Marxist theory on social class and culture stratification as its basis of the theory. Looking at the primary data taken from the movie, it is proven how social class and culture stratification affects art status and marriage approval. Circus as art is considered lower class art because it is cheap and historically poor just like it is rejected in the movie. Marriage approval is also affected by social class on how different class cannot marry because they would be not considered as not family member anymore. Industrial revolution as the beginning of all social class affect many things until today as what is depicted in the movie.